THE IMPACT OF EXTENSIVE READING ON VOCABULARY ACQUISITION AND LEXICAL DIVERSITY IN EFL LEARNERS’ WRITING - Hikmatova Charos; Kattaboyeva Dilrabo Kattaboyevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This study investigates the impact of extensive reading on vocabulary acquisition and lexical diversity in EFL learners’ writing. Through standard presentation to wealthy and changed writings, learners create more grounded word acknowledgment, more profound lexicon information, and an expanded capacity to utilize differing lexical things in composed errands. The discoveries show that broad perusing not as it were upgrades lexical run but moreover makes strides in general composing quality. The consider concludes that joining broad perusing into EFL programs is an compelling approach to cultivating more progressed and shifted composed dialect.